Therapeutic implications of thymoquinone and its molecular and functional mechanisms against oral and lung cancer - Tabassum, Shabana; Thakur, Vikram; Norhayati, Rosli; Solachuddin Jauhari, Arief Ichwan; Mishra, Puranjan; Wastuti Hidayati, Suriyah (Elsevier, 2022)
Thymoquinone, a bioactive component of the black seed of Nigella sativa, has received great attention from researchers due to its wide spectrum of pharmacological potentials. The present review highlights the molecular and functional mechanisms of thymoquinone serving as a therapeutic molecule combating oral and lung cancer by following the most recent literature. This summarized the latest nanotechnological interventions enhancing the efficacy and availability of thymoquinone in the in-vitro and in-vivo cancer models. Thymoquinone exhibits a significantly promising anticancer effect against oral and lung cancer by prompting intrinsic and extrinsic pathways of apoptosis through the activation of different caspases cascades, up and downregulation of apoptotic genes, antitumor cell proliferation, ROS regulation, etc. The accomplished insight into molecular and functional mechanisms of thymoquinone particularly combating oral and lung cancer will provide a better understanding and exploration of thymoquinone in an ethnopharmacological context.